Study on the resistivity characteristics and mechanism of silt clay under different initial conditions - Chundong Wang; Fuming Bao; Youqian Lu (PLoS ONE, 2025)
By taking silt clay as the research object, two-phase electrode resistivity tests under different water content and dry density conditions were carried out to clarify the resistivity variation law and influence mechanism of silt clay. The results show that the resistivity of the soil decreases sharply in the low moisture content section then tends to stabilize with the change of moisture content, and decreases continuously with the increase of dry density. There are three phases of a medium, namely soil, water and air, in unsaturated soil, so there are mainly three conductive paths: between soil particles, between pore fluids, and between soil-water coupling. Under different moisture content and dry density conditions, there are obvious differences in the effective contact area, and the types and numbers of conductive paths, which in turn affect the resistivity of the soil. The water status and pore structure of the silt clay samples were analyzed by hydrogen nuclear magnetic resonance (1H-NMR) results to clarify the conductive mechanism of unsaturated silt clay. Finally, a volumetric moisture content and resistivity model is established to unify the effects of moisture content and dry density on resistivity, providing a theoretical reference for the construction and operation safety of silt clay engineering.